"Geologic issues: Community impacts and science communication"—An introductory geoscience assignment designed to help underrepresented minority students see value in the geosciences. Issue 4 (2nd October 2019) - Reinen, Linda A.; Kortz, Karen M.
Abstract: Responding to the need for recruitment and retention of a diverse geoscience population, we developed a capstone homework assignment for use in introductory-level geoscience courses. In this article we present "Geologic Issues: Community Impacts and Science Communication, " a place- and problem-based assignment designed using research on student learning and interest, as well as research that suggests underrepresented minority students are more likely to be attracted to science disciplines if they perceive that science can be used to help their communities. The assignment combines a socially relevant problem in a location of personal interest for each student with a short letter-writing assignment designed to help students recognize the value and applicability of the geosciences to their lives. This assignment was successfully implemented in two very different settings—a highly selective four-year college and an open-access two-year college—and to diverse populations of students in small and moderate-sized classes. Students who participated in the study reported positive influences this assignment made on their perceptions of geoscience. For example, the assignment helped them (a) realize that geoscience was pertinent to their community (100% of students); (b) feel more confident in using and communicating science (95% of students); and (c) potentially see themselves as geoscientists because of interest, perception of the value of geoscience, and learning that geoscientists can work in their communities. These results are independent of academic setting, gender, and racial and ethnic diversity, indicating that all groups of students participating in the study benefitted from the assignment.